The Theo-Management Model: An Investigation into The Implementation and Impact of Islamic Corporate Culture at LP3I Purwokerto - Hartono; Novan Ardy Wiyani; Nurfuadi (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2023)
This study explores the implementation of theologically-based, or